STUDY OF ELASTIC AND INELASTIC SCATTERING OF DEUTREONS BY 13C NUCLEI AT ENERGY Ed=18 MeV - Zh.K. Kerimkulov; N. Burtebayev; D.M. Janseitov; A.S. Demyanova; L.I. Galanina; D.K. Alimov; Y.S. Mukhamejanov; N. Amangeldi; M. Nassurlla; А. Aimaganbetov; Y. Nurtazin; K. Talpakova; et al. (Academic Scientific Journal of Computer Science, 2019)
The differential cross sections of elastic and inelastic (3/2– excited state of 13С, Ex = 3.684 MeV) scattering of deuterons by 13С nuclei at energy Ed = 18 MeV in the angular range θlab = 10o-75o have been measured at the U-150M cyclotron (Almaty, Kazakhstan). The total error of the experimental data obtained does not exceed 10%. The standard dE-E method of registration and identification of interaction products was used in the experiment. Thin carbon films with a thickness of about 150 μg/cm2 of about 80% enrichment by 13C were used as targets. A theoretical analysis was made within the framework of the optical model of the nucleus and the coupled channels method. The values of the quadrupole deformation were determined, which are in good agreement with the literature data. It is shown that in order to improve the theoretical description of experimental data, additional mechanisms (reactions, other inelastic processes) that can influence the formation of scattering cross sections must be taken into account in the calculations.